Pengambilan Keputusan Investasi Terhadap Nilai Perusahaan Jasa Perbankan Yang Terdaftar Pada BEI - Rifqiansyah, Rifqiansyah; Nurfaisah, Nurfaisah; Samsuri, Samsuri; Pertiwi, Hardianti (Universitas Musamus,Merauke,Papua, 2024)
This study aims to examine the effect of investment decisions on the value of financial services companies listed on the Indonesia Stock Exchange (IDX), which is reflected through the investment opportunity set (IOS). The type of research used is quantitative, with a sample of 110 companies. The data analysis technique used is multiple linear regression to identify the relationship between investment decision variables and company value. The independent variables used include various investment decision metrics, such as Total Assets Growth, Current Assets to Total Assets Ratio, Market to Book Assets Ratio, Earnings to Price Ratio, and Capital Expenditure to Book Value of Assets Ratio. The results of the study indicate that the value of financial services companies is not affected by investment variables measured using Total Assets Growth and Current Assets to Total Assets Ratio. However, the Market to Book Assets Ratio, Earnings to Price Ratio, and Capital Expenditure to Book Value of Assets Ratio are proven to significantly affect the value of banking services companies listed on the IDX. Overall, investment decision indicators have a significant effect on company value. This study contributes to the financial literature by emphasizing the importance of investment metric analysis in increasing the value of financial services companies in Indonesia. These findings are also relevant for policy makers and financial managers in determining optimal investment strategies.